A Multiverse of Knowledge: Cultures and IR Theories. (6th November 2018) - Qin, Yaqing
Abstract: This article develops a cultural approach to international theorizing. It argues that a cultural community is the prototype of a community of practice and where, therefore, shared background knowledge plays a significant role in knowledge production and theoretical innovation, because theorists are cultural beings sharing the background of the community in which they live and practice. Social theory, thus, bears the indelible cultural imprints of that community. It correctly aims to be universal but can at best achieve bounded universality. Two cases are used to illustrate the cultural approach: the 'implicit permeation' typical of Western (international relations) international relations theories, which are inspired by key elements of Western culture, history, and practice and the 'explicit penetration' of Chinese IR theories, which rely explicitly on Chinese cultural resources for information and enlightenment. Three Chinese IR theories—Yan Xuetong's moral realism, Zhao Tingyang's Tianxia system, and Qin Yaqing's relational theory—are discussed as specific examples. The cultural approach is both essential and effective for the development of non-Western IR theories. Taking a pluralistic approach, the article also argues for the recognition of a multiverse of knowledge and for the encouragement of non-Western IR theories to grow and engage Western IR theories in a constructive dialog toward reciprocal empowerment. A significant development upon the discipline's centenary would, perhaps, be the rise of a truly global IR project whose hallmark is the growth of non-Western IR theories.